2014
DOI: 10.4103/0975-9476.131738
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic, sedative, and hypnotic activities of aqueous extract of Morinda citrifolia fruit

Abstract: Morinda citrifolia (Indian mulberry or noni) fruit has been long used as a folk medicine for a wide range of health purposes as it is claimed to have analgesic, antiinflammatory, antioxidant, detoxifier, and cell-rejuvenator properties. A recent study has revealed central nervous system suppressant nature of its extract. Hence, the present study has evaluated the anxiolytic, sedative, and hypnotic effects of the aqueous extracts of Morinda citrifolia in rodents in comparison to diazepam. Anxiety was assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The fruit extract can be seen as a target for anxiety disorders, as it has a reported effect when provided as a food supplement in an animal model (Kannan et al , ). But the need to also consider the toxic effects that the fruit may have in the body should be noted (Tin and Wiwanitkit, ).…”
Section: Anxiolytic Activitymentioning
confidence: 99%
“…The fruit extract can be seen as a target for anxiety disorders, as it has a reported effect when provided as a food supplement in an animal model (Kannan et al , ). But the need to also consider the toxic effects that the fruit may have in the body should be noted (Tin and Wiwanitkit, ).…”
Section: Anxiolytic Activitymentioning
confidence: 99%
“…It was found that if the drug had the sedative property then there was less disruption of the beams of light in the actophotometer as the rodents did not try to explore much because of the sedation. 14 On the other hand, stimulants had the opposite effect. 15 The Withania coagulans was not explored much for its central nervous system (CNS) depressant effect.…”
Section: Introductionmentioning
confidence: 99%
“…Each part of the plant, from its roots to its seeds, is widely used in folk medicine, and several therapeutic effects have already been reported. 7 Biological actions of M. citrifolia include antioxidant, 8 immunostimulatory, 9 antitumor, 10 antidiabetic, 11 anti-obesity 12 antibacterial and anti-septic, 13,14 antifungal, 15 antiviral, 16 leishmanicidal, 17 anti-inflammatory, 18 antinociceptive and analgesic, 19 neuroprotective, 20 wound healing, 21 anti-allergic, 22 antiangiogenic, 23 antiemetic and anti-nausea, 24 anti-gastric ulcer and oesophagitis, 25 anthelmintic, 26 antimutagenic, 27 antipsychotic, 28 anxiolytic, 29 photo protective, 30 anti-wrinkle 31 and periodontal tissue regeneration activities 32 have been reported. In the present study, we hypothesized the beneficial effect of Noni (Morinda citrifolia L.) in reducing blood pressure in ovariectomized rats fed with high-fat diet.…”
Section: Introductionmentioning
confidence: 99%